Effect of UV light polymerization time on the properties of plastic crystal composite polyacrylate polymer electrolyte for all solid‐state lithium‐ion batteries. Issue 16 (9th December 2021) - Zhang, Shujian; Lu, Yang; He, Kewu; Meng, Xianghui; Que, Lanfang; Wang, Zhenbo
Abstract: To solve the issues of low ionic conductivity, poor interfacial stability, and weak mechanical strength in the current polymer electrolytes, herein, the UV curing method is proposed to in‐situ polymerize the plastic crystal composite solid polymer electrolyte (S‐PCCE). By using ethoxylated trimethylolpropane triacrylate (ETPTA) as polymerization monomer, in conjunction with the butadiene nitrile and other additives, the S‐PCCE is prepared under ultraviolet light. The S‐PCCE shows improved ionic conductivity than other solid electrolyte materials. The ionic conductivity at room temperature can reach 0.98 × 10 −3 S/cm, and it can reach 2.8 × 10 −3 S/cm at 55°C, which is beneficial to achieve high battery performance. The LiFePO4/S‐PCCE/Li battery has a high initial discharge specific capacity of 150.4 mAh/g at 0.2C, and the highest discharge specific capacity can reach 162.5 mAh/g. Moreover, after 100 cycles, the battery can still maintain a high discharge specific capacity of 154.2 mAh/g, with a Coulomb efficiency of 98.4%. At the same time, the electrolyte has excellent high‐temperature adaptability, and can still work stably at 55°C with improved ionic conductivity. The superior performance of this material indicates that the plastic crystal composite polyacrylate solid electrolyte based on UV curing method can be used to prepare a high‐performance lithium‐ion battery, and this technology can also be compatible with existing lithium‐ion battery equipment. Abstract : To solve the issues of low ionic conductivity, poor interfacial stability, and weak mechanical strength in the current polymer electrolytes, herein, the UV curing method is proposed to in‐situ polymerize the plastic crystal composite solid polymer electrolyte (S‐PCCE). At the same time, the influence of UV irradiation time on the performance of electrolyte was discussed in detail.